Observing the products of stellar evolution in the old open cluster M67 with APOGEE - Bertelli Motta, Clio; Pasquali, Anna; Grebel, Eva K. (Monthly notices of the Royal Astronomical Society, 2017)
Recent works have shown how the [C/N] ratio in stars after the first dredge-up (FDU) can be used as an age estimator in virtue of its dependence on stellar mass. For this purpose, precise predictions of the surface chemical composition before and after the mixing takes place in the convective envelope of subgiant stars are necessary. Stellar evolution models can provide us with such predictions, although a comparison with objects of known age is needed for calibration. Open clusters are excellent test cases, as they represent a single stellar population for which the age can be derived through, e.g. isochrone fitting. In this study, we present a detailed analysis of stars belonging to the well-known open cluster M67 observed by the Apache Point Observatory Galactic Evolution Experiment (APOGEE) survey in the twelfth data release of the Sloan Digital Sky Survey and whose chemical properties were derived with the APOGEE Stellar Parameters and Chemical Abundances Pipeline. We find that the [C/N] abundance of subgiant branch stars is overestimated by ∼0.2 dex due to an offset in the determination of the [N/Fe] abundance. Stars on the red giant branch and red clump are shown not to be affected by this offset. We derive [C/N]FDU = −0.46 ± 0.03 dex, which poses a strong constraint on calibrations of [C/N]FDU as age indicator. We also do not find any clear signature of additional chemical mixing processes that set in after the red giant branch bump. The results obtained for M67 indicate the importance of conducting high-resolution spectroscopic studies of open clusters of different ages in order to establish an accurate age-dating method for field stars.
Published online: 14 December 2016
Gesehen am 04.09.2017